Revitalización del espacio público como estrategia para la integración del barrio Cándido Leguízamo con sectores urbanos circundantes (2021)
This research presents information Abstract collected through observation and primary and secondary sources, to investigate and deepen the description of a specific study territory, its needs, problems and potentialities, in order to propose solutions to improve quality from the architecture. urban life of its inhabitants, through sustainable development, which generates belonging and social cohesion by caring for the environment as a fundamental support for different social activities. The territory as an urban context and the importance of its use , to generate positive and balanced transformations between the different systems that make up the city. Neiva is a city that is growing rapidly and has a significant public space problem, with only 3.1 m2 per inhabitant, well below the 15m2 recommended by the WHO per inhabitant. It is imperative to plan its growth, to generate quality public space for its inhabitants. “The planning of urban space is imposed as an unavoidable means for improving the quality of life of the population; in particular, a specia l attention to public spaces contributes to crime prevention and becomes the urban support of public security.